Effect of covert recordings from vehicles on the performance of forensic automatic speaker recognition - Künzel, Hermann J. (International Journal of Speech, Language and the Law, 2017)
Speech recordings made in vehicles with hidden recording devices (“bugs”) present a number of peculiarities compared to high-quality direct microphone recordings, and also ordinary mobile phone recordings. Inspired by a recent court case the present investigation was undertaken to quantitatively assess the effect of three types of covert recordings, including data transmission, on a widely-used forensic automatic speaker recognition (FASR) system (Batvox 3.1). Using simultaneous high-quality re-recording of speech samples from 50 speakers played back inside four automobiles and one 5-ton RV as a benchmark, equal-error rates (EERs) between zero and 2 % were found. The latter number was obtained for GSM-transmitted voice data. When the acoustic data were not transmitted but stored inside the covert recording device, or recorded and stored on a smartphone placed inside the vehicles, EERs between zero to 0.45 % were obtained. Generally, EERs are similar to those obtained using the same FASR system in studies with non-covert recordings (direct recordings, landline and mobile telephone). No effect of the type or model of the vehicles on EERs was observed.